Kaum perempuan dan partisipasinya dalam pemerintahan desa - Akbar Pandu Dwinugraha (Publisia: Jurnal Ilmu Administrasi Publik, 2019)
The purpose of this research is to find out how far women are involved in village governance. This research uses descriptive qualitative and quantitative research types or better known as combination research. The research location is the Malang Regency administration area in the period January-August 2017. Based on the results of data collection and analysis in the field, it can be concluded that (1) Women's participation in coaching, empowering and providing opportunities in terms of conveying aspirations to the government has been carried out in Malang Regency, This is without exception carried out in under developed, developed and advanced. (2) Opportunities for women to be elected / nominated as village heads, village officials, members of the BPD (Village Consultative Organization) and LKD (Village Community Institutions) starting from the underdeveloped, developed and advanced, wide open and there is no difference in access given to the wider community. (3) Women in the underdeveloped, developed and advanced have received protection from the disruption of peace in the village, have received maximum fair services and received information about village development plans and implementation by the village government. (4) Women in the underdeveloped, developed and advanced villages are given the same rights in overseeing village government, are involved in village deliberations and are given the same opportunity to submit complaints about village development planning and implementation to the village government.DOI: https://doi.org/10.26905/pjiap.v4i2.3376